Real-World Outcomes of Hodgkin Lymphoma: A Multi-Centric Registry From India - Bhurani, Dinesh; Nair, Reena; Rajappa, Senthil; Rao, Suparna Ajit; Sridharan, Nithya; Boya, Rakesh Reddy; Raman, Ganapathi S.; Menon, Hari; Seshachalam, Arun; Nimmagadda, Ramesh (Frontiers in Oncology, 2022)
BACKGROUND: Hodgkin’s lymphoma (HL) is one of the most curable malignancies with a 5-year survival of over 80%. Most published literature from low-middle income countries comes from single institute experience. METHODOLOGY: OncoCollect Lymphoma group registry was set up in 2017, and has 9 major participating sites across India. Data of newly diagnosed Classical HL (CHL) patients, treated between 2011 to 2017 was collected using OncoCollect software. The clinical features, subtypes, prognostic stratification, treatment patterns, response to first-line treatment and 5-year outcomes were analyzed. All statistical analysis was done using Microsoft R Open statistical software linked to OncoCollect software. RESULTS: There were 939 newly diagnosed CHL patients with a median age of 38 (range, 18-99) years at presentation. The male to female ratio was 2.07:1. Histological subtypes included: Mixed-cellularity, CHL (MC, CHL), Nodular-sclerosis, CHL (NS, CHL), Lymphocyte-rich, CHL (LR, CHL) and Lymphocyte-depleted, CHL (LD, CHL), in 60.60%, 26.94%, 9.80%, 2.66% respectively. At presentation, 50.43% had B symptoms and 53.35% had advanced disease. 29.71% of advanced stage patients had high Hodgkin IPI score. 79% and 21% of patients received 1st line treatment with chemotherapy alone or combined modality treatment with chemotherapy and radiotherapy. The most common first-line chemotherapy was ABVD based regimen (94.68%). The overall response rate was 93.48%. Complete response rates among early stage favourable and unfavourable risk group were 92.73%, 86.79%, and among advanced stage low and high-risk group were 76.64%, 69.78% respectively. The median relapse free follow-up duration was 51 Months (IQR 22-69). Significant difference was found in 5-year EFS between the early vs advanced stage disease 83.53%, 73.55% (p = 0.00087). Similarly, significant difference was found in EFS among early-stage patients treated with a combination of 4 cycles chemotherapy and radiotherapy vs chemotherapy alone 88.57%, 66.33% (p=0.0042). CONCLUSIONS: In this large cohort from India, survival of patients with HL was comparable to the developed world. With a median follow up of 51 months the 5-year EFS and OS of all patients was 78.24 % and 83.63 %, respectively.